DAMPINGAN PEMAHAMAN FIQIH WANITA: PENGETAHUAN TENTANG DARAH HAID DI DESA SEMAMBUNG - Faisal Faliyandra; Lailatul Hasanah; Nur Safiatun; Lailatul Akmaliyah; Kamilatul Ilmiyah (LP2M Universitas Ibrahimy, 2021)
The problem of women's fiqh, specifically the practice and concept of menstrual blood, is the main problem in Semambung Village, so it is very important to overcome these problems. So the focus of the assistance that will be carried out is to provide an understanding of the concept and practice of menstrual blood which is part of women's fiqh. The method used in community service uses PAR (Participatory Action Research). There are several results from this assistance that have changed the social conditions of the community, such as; 1) growing awareness of women about menstruation; 2) there is a change in attitudes from various community and religious leaders in the form of social support for program implementation. Hopefully in the future, there will be research on the important role of community and religious leaders on programs related to religious understanding.